Case Study of line loss Reduction in TNEB Power Grid - S. Sambath; P. Palanivel; C. Subramani; S.P.K. Babu; J. Arputhavijayaselvi (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Unbundling of Electricity Boards in India into small units (corporations) have created opportunities for involvement of independent power generation companies. Remarkable achievements and improvements are expected in power quality especially in the southern part of the country where more power shortage, power quality low and serious power losses along the transmission and distribution lines of the power system. The power system utilities are increasing every day, to enhance the distribution power quality and maintain the voltage stability is a challenging task in the complex distribution. This can be achieved through the Distributed Generation (DG). DGs are the final link between the high voltage transmission and the consumers. This will effectively improve the active power loss reduction. This paper represents the technique to enhance the power qualities and minimize power losses in a distribution feeder by optimizing DG model in terms of size, location and operating point of DG. The proposed technique has been developed with considering load characteristics and representing constant current model. The effectiveness of the proposed technique is tested and verified using MATLAB software on long radial distribution system in Tamil Nadu (India).